Time Travel Proxy: Using Lightweight Video Recordings to Create Asynchronous, Interactive Meetings - Tang, John; Marlow, Jennifer; Hoff, Aaron; Roseway, Asta; Inkpen, Kori; Zhao, Chen; Cao, Xiang (CHI 2012, 2012)
Time Travel Proxy (TTP) enables participating in meetings that you cannot attend in real time, either because of time conflicts or global time zone differences. TTP uses lightweight video recordings to pre-record your contributions to a meeting, which are played on a tablet that serves as a proxy for you during the meeting. Reactions and responses in the meeting are also captured in video to give you feedback of what happened at the meeting. A working prototype of TTP was deployed and studied within four developer teams in their daily stand-up meetings. The study found that the affordances of video helped integrate the time traveler into the social context of the meeting, although the current prototype was better at enabling the time traveler to contribute to the meeting than it was in conveying the meeting experience back to the time traveler.